MHD flow and heat transfer of ferrofluid on stagnation point along flat plate with convective boundary condition and thermal radiation effect - Siti Hanani, Mat Yasin (IOP Publishing, 2019)
This theoretical study deals with numerical solution of MHD convection laminar boundary layer flow and heat transfer on stagnation point along a stationary horizontal flat plate. For this purpose, ferrofluid which contains magnetite, Fe3O4 as a ferroparticles and water as a base fluid is considered. Ferrofluid has shown a particular achievement when the effect of external magnetic field applied, such as helping to control the properties of physical and flow of ferrofluid. The study starts with the formulation of the mathematical equations that governed the ferrofluid flow and heat transfer. The governing equation which is in the form of dimensional nonlinear partial differential equations are reduced to nonlinear ordinary differential equations by using appropriate similarity transformation and then solved numerically by using the Keller-box method. Numerical result is discussed in terms of pertinent effects that influence the ferrofluid flow and heat transfer like magnetic parameter, ferroparticles volume fraction parameter, Biot number and radiation parameter on velocity and temperature profiles. It is found that the temperature profile increase with an increase volume fraction of ferroparticles parameter, radiation parameter and Biot number and decrease with increasing magnetic parameter.